GATA2 deficiency syndrome: A decade of discovery. Issue 11 (31st August 2021) - Homan, Claire C.; Venugopal, Parvathy; Arts, Peer; Shahrin, Nur H.; Feurstein, Simone; Rawlings, Lesley; Lawrence, David M.; Andrews, James; King‐Smith, Sarah L.; Harvey, Natasha L.; Brown, Anna L.; Scott, Hamish S.; et al.
Abstract: GATA2 deficiency syndrome (G2DS) is a rare autosomal dominant genetic disease predisposing to a range of symptoms, of which myeloid malignancy and immunodeficiency including recurrent infections are most common. In the last decade since it was first reported, there have been over 480 individuals identified carrying a pathogenic or likely pathogenic germline GATA2 variant with symptoms of G2DS, with 240 of these confirmed to be familial and 24 de novo. For those that develop myeloid malignancy (75% of all carriers with G2DS disease symptoms), the median age of onset is 17 years (range 0–78 years) and myelodysplastic syndrome is the first diagnosis in 75% of these cases with acute myeloid leukemia in a further 9%. All variant types appear to predispose to myeloid malignancy and immunodeficiency. Apart from lymphedema in which haploinsufficiency seems necessary, the mutational requirements of the other less common G2DS phenotypes is still unclear. These predominantly loss‐of‐function variants impact GATA2 expression and function in numerous ways including perturbations to DNA binding, protein structure, protein:protein interactions, and gene transcription, splicing, and expression. In this review, we provide the first expert‐curated ACMG/AMP classification with codes of published variants compatible for use in clinical or diagnostic settings. Abstract : GATA2 mutation update including a comprehensive deconvoluted summary of all published germline GATA2 deficiency syndrome mutations to date, associated phenotypes, and expert ACMG/AMP classification (with criteria) of all 179 pathogenic and likely pathogenic unique variants.